High-performance Magnetoimpedance Sensors in Micropatterned Multi-meander Line Designs - Thi Thanh, Ngo; Van Tuan, Nguyen; Huy Hoang, Dang; Minh Vuong, Pham; Si Hong, Hoang; Duy Phu, Do; Anh Tam, Ho; Nguyen Thuc, Vu; Giang, Do Thi Huong (VNU Journal of Science: Mathematics - Physics; Vol 41 No 3DO - 10.25073/2588-1124/vnumap.5002, 2025)
In this work we present the design and fabrication of micro-scale magnetoimpedance (MI) sensors based on FeSiC soft magnetic ribbon, using laser engraving and chemical etching to create conventional meander (1M), meander structures in parallel (4Mpa) and perpendicular (4Mpe) configurations. Experimental characterization and finite element simulations revealed that assembling four meander elements enhances the MI effect by up to an order of magnitude compared to the 1M sensor. The 4Mpa configuration exhibits strong anisotropic MI response and lower frequency resonance of 1.5 GHz, while the 4Mpe structure offers a slightly lower MI ratio of 180% but with near-isotropic behavior. These differences arise from uniaxial versus multi-axial magnetic anisotropy, respectively, thanked to the numerical simulation. The results demonstrate that sensor performance can be tailored by selecting appropriate meander arrangements, enabling enhanced sensitivity and directional control for diverse applications in biomedical, industrial, and high-frequency sensing fields.